Early life exposure to diagnostic radiation and ultrasound scans and risk of childhood cancer: case-control study. (10th February 2011) - Rajaraman, Preetha; Simpson, Jill; Neta, Gila; Berrington de Gonzalez, Amy; Ansell, Pat; Linet, Martha S; Ron, Elaine; Roman, Eve
Abstract : Objective To examine childhood cancer risks associated with exposure to diagnostic radiation and ultrasound scans in utero and in early infancy (age 0-100 days). Design Case-control study. Setting England and Wales. Participants 2690 childhood cancer cases and 4858 age, sex, and region matched controls from the United Kingdom Childhood Cancer Study (UKCCS), born 1976-96. Main outcome measures Risk of all childhood cancer, leukaemia, lymphoma, and central nervous system tumours, measured by odds ratios. Results Logistic regression models conditioned on matching factors, with adjustment for maternal age and child's birth weight, showed no evidence of increased risk of childhood cancer with in utero exposure to ultrasound scans. Some indication existed of a slight increase in risk after in utero exposure to x rays for all cancers (odds ratio 1.l4, 95% confidence interval 0.90 to 1.45) and leukaemia (1.36, 0.91 to 2.02), but this was not statistically significant. Exposure to diagnostic x rays in early infancy (0-100 days) was associated with small, non-significant excess risks for all cancers and leukaemia, as well as increased risk of lymphoma (odds ratio 5.14, 1.27 to 20.78) on the basis of small numbers. Conclusions Although the results for lymphoma need to be replicated, all of the findings indicate possible risks of cancer from radiation at doses lower than those associated with commonly used procedures such as computed tomography scans, suggesting the need for cautious use of diagnostic radiation imaging procedures to the abdomen/pelvis of the mother during pregnancy and in children at very young ages.